Automobile Design and Implementation of CAN bus Protocol- A Review - Chikhale, Shahu N (IJRDO - Journal of Electrical And Electronics Engineering, 2018)
Controller area network (CAN) most researched communication protocol used for automotive industries. Now we are heading towards the automotive world of autonomous AI based or semiautonomous vehicle system which is capable of delivering the best in class driverless experience around the world. We need an effective implementation of vehicle and computer convergence along with a very fast communication protocol. CAN helps us to design and implement such kind of system with a single onboard computer which controls vehicle parameters remotely. Researchers are looking forward to Wireless Controller Area Network (WCAN) which eventually can even prospect into the IOT field and flourishes the smooth transportation system. This paper reviews such kind of design and implementation setups to acquire a secured and effective CAN bus protocol